Araby [videorecording (DVD)] - Dumans, João; Dumans, João; Uchôa, Affonso; Uchôa, Affonso; Sousa, Aristides de; Caliari, Murilo; Cabal, Renata (Grasshopper Films, 2019)
When teenager Andre is asked to pick up clothing and documents at the home of sick factory worker Cristiano, he reads Cristiano's journal and learns about the fascinating journey of his life.